MEASUREMENT PALM OIL AS BIOLOGICAL ASSETS USING PSAK 69 THAT ADOPT IAS 41 - Siahaan, Audrey Margareth (Lembaga Jurnal & Seminar Universitas Pembangunan Panca Budi, 2021)
IAI has just implemented PSAK 69 which is the adoption of IAS 41. Indonesia has a large oil palm plantation, which requires an assessment of reliable biological assets. The use of fair value in accordance with PSAK 69 wants to be seen to be implemented or not. The researcher used a literature study to see how IAS 41 was adopted by PSAK 69 in various countries. Of the 9 journals analyzed only one said that fair value can be relied on compared to historical value. Fair Value is very difficult to use because there are several constraint factors. Therefore, the assessment of FFB which is an agricultural product from oil palm has a variety of acquisition values in accordance with the location of the plantation area.